2014
DOI: 10.1038/srep06589
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism of metal-oxide nanowires synthesized by electron beam evaporation: A self-catalytic vapor-liquid-solid process

Abstract: We report the growth mechanism of metal oxide nanostructures synthesized by electron beam evaporation. The condensed electron beam can easily decompose metal oxide sources that have a high melting point, thereby creating a self-catalytic metal nanodot for the vapor-liquid-solid process. The metal oxide nanostructures can be grown at a temperature just above the melting point of the self-catalyst by dissolving oxygen. The morphology of nanostructures, such as density and uniformity, strongly depends on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…At temperatures above the eutectic point it is observed the formation of nanowires with identical composition to the base components used in the growth process. All the nanowires have the catalyst particle at their tips, which can be observed in Figure 1 b and has been confirmed to be made of the same material as the nanowire by micrograph techniques [ 35 ], thus supporting the self-catalytic VLS hypothesis [ 41 , 42 , 43 ].…”
Section: Growth Of Ito Nanowires Characteristics and Dependencessupporting
confidence: 58%
See 1 more Smart Citation
“…At temperatures above the eutectic point it is observed the formation of nanowires with identical composition to the base components used in the growth process. All the nanowires have the catalyst particle at their tips, which can be observed in Figure 1 b and has been confirmed to be made of the same material as the nanowire by micrograph techniques [ 35 ], thus supporting the self-catalytic VLS hypothesis [ 41 , 42 , 43 ].…”
Section: Growth Of Ito Nanowires Characteristics and Dependencessupporting
confidence: 58%
“…Similar results were obtained by Kumar et al [ 35 ], who grew ITO nanowires also by EBE, by Fung et al [ 39 ], who produced ITO nanowires by dc sputtering, and by Johnson et al [ 40 ] using CVD. Authors that have reported the fabrication of ITO nanowires have described two mechanisms for growing such nanostructures: vapor–liquid–solid (VLS) and self-catalytic VLS [ 41 , 42 , 43 ]. The first one requires relatively high growth temperatures, normally ranged between 700–1000 °C.…”
Section: Growth Of Ito Nanowires Characteristics and Dependencesmentioning
confidence: 99%
“…32 At an oxygen partial pressure of 10 − 4 Torr, e-beam irradiation can decompose ITO to indium, tin and oxygen.…”
Section: Fabrication Of Ito Branchesmentioning
confidence: 99%
“…On the cross-section view of the NCO-1/1 sample ( Figure 4 d bottom), nanowire crystals can be easily observed, reaching lengths up to 40 nm. Several mechanisms of the nanowire/whiskers growth are presented in the literature, describing the morphology of the sample NCO-1/1 [ 65 , 66 , 67 ], including the growth of metal-oxide whiskers [ 68 , 69 , 70 ]. During the formation of TMO nanowires, the importance of the chemical composition and growth conditions were noted [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%